A Comparison of Industrial Concentration in the United States and Britain - Shepherd, W. Geoffrey (The Review of Economics and Statistics, 1961)
There are several major reasons why general levels and patterns of concentration in United States and United Kingdom manufacturing industry might be expected to differ; among them are size, economic history, growth patterns, international trade, and anti-monopoly policy. Assuming similar technology of production in both countries, smaller domestic markets (in terms of geography and level of demand) would make for higher concentration ratios in the United Kingdom, since fewer optimal-size firms would suffice for each industry.1 Of course, past technological trends may have offset this, by evolving lower optimal firm sizes, such as the British system of shorter runs as against American mass production. Britain's greater maturity, and the widespread rationalization waves in the last two generations, would point toward higher British ratios. As for growth patterns, Britain's higher proportion of basic manufacturing trades (metals and heavy engineering), where economies of scale may be greatest, might also indicate a higher general level of concentration. Britain's greater involvement in international trade probably is important for individual industries, though its effect on concentration ratios might go either way. And Americans might suppose that United States anti-trust policy has kept the ratios relatively lower there than in the United Kingdom (though anti-trust vigor may merely reflect a largely ideological, and token, effort against an especially grave concentration problem). Other reasons one way and the other could easily be added. With all the difficulties of measurement and comparison that plague this topic, and with all the counterpoised influences in the two countries, it is surprising that one recent comparison, by P. Sargant Florence in I953 dealing with the year I935, reaches the straightforward conclusion that on the whole American manufacturers are roughly equally in control as are the British.2 In contrast, Rosenbluth in I952 reached different conclusions for the same year, I935, on the basis of a frequency of employment in manufacturing industries by degree of concentration.3 In each iO per cent bracket, cumulative United Kingdom employment as a per cent of the total exceeded that in the United States; in short, more employment was in more highly concentrated industries. It is clear therefore that the general level of concentration is higher in the British industries.4 As for patterns of concentration in sectors and industries, Florence found a remarkable association between specific industry ratios, whereas Rosenbluth's figures for matched industries tended to show important differences. Whatever the truth about comparative concentration in the United States and the United Kingdom (and whatever such a comparison may mean), the discrepancy and obsolescence of these conclusions suggest a need for more research, especially concerning more recent years. Now that two new sets of ratios for a fairly recent year (195 i) are available, a new Transatlantic comparison is bound to be made. This paper, it is hoped, provides it. Methods. The methods used in this paper are intuitively simple.5 In the British data from Evely and Little, industries are classified according to the degree of concentration of their employment in the largest three firms, and this gives a frequency dispersion with ten ten-per-cent categories.6 For the United States a similar tabulation for the same year (195I) has been drawn from that rich volume of data com-